Propagation of a Flat-topped Gaussian beam in Softly Violent Atmospheres and Estimation in Near Field - Khamees, Hussein Thary; Salloom, Hussein T.; Akram, Israa N. (Edelweiss Applied Science and Technology, 2024)
We investigate the analysis of optical communication employing the shape beams, definitely concentrating on the effect of factors on the physical characteristics of a Flat Top Gaussian (FTG) beam. The propagation of a beam of laser light in the atmosphere layer is disposed to being affected by many optical phenomena such as scattering, absorption, and turbulence. These phenomena arise from differences in the scintillation index and the intensity modes realized in the source and receiver planes. This work is a numerical investigation of the FTG laser beam as it beams trekking through a zone of low turbulence using open-source software. This simulation will be conducted using a mathematical model derived from the split-step beam propagation technique. The intensity distributions of the source plane and the average intensity is received in air turbulence are computed, with an extra contour at the transducer plane. The Rytov approach to develops the scintillation index, structural constant, source size, and supplementary parameters to measure the weak turbulent model. Furthermore, these factors are studied in the context of near-field propagation. Also, the impression of the scintillation and wander of the beam is assessed. All simulated results are analyses and contrasted with the TEM00 Gaussian beam. At last, these discoveries are compared with the data obtained in the experimental piece of the study, additionally by applied in laser applications.